Effects of Zoledronic Acid on Physiologic Bone Remodeling of Condylar Part of TMJ: A Radiologic and Histomorphometric Examination in Rabbits - Ufuk Tatli; Yakup Üstün; Mehmet Kürkçü; Mehmet Emre Benlidayı (The Scientific World Journal)
Objective. The purpose of the present study is to evaluate the effects of systemically administered zoledronic acid (ZA) on the physiological bone remodeling and the microarchitectural parameters of the condylar part of TMJ in a rabbit model. Study Design. Thirty skeletally mature male New Zealand white rabbits were randomly divided into two groups. The experimental group was administered an intravenous, single dose of 0.1 mg/kg ZA diluted with 15 mL of saline in a 15-minute perfusion with an infusion pump. The control group was administered only saline infusion for 15 minutes. All rabbits were sacrificed on the 21st postoperative day. Radiodensitometric and histomorphometric examinations were performed on the harvested mandibular condyles. The data were analyzed statistically. Results. Radiodensitometric findings showed that ZA treatment resulted in a significant increase in the mineralization of mandibular condyle. This result was supported by the histomorphometric findings. Conclusion. The present study has revealed that a temporary delay in the physiological bone remodeling using single dose of ZA increases bone mineral content and makes the microarchitecture of the mandibular condyle more compact. These effects may be regarded as base data and considered in numerous clinical situations including TMJ.